In vivo genetic stability of Salmonella typhi detected by ribotyping and pulsed field gel electrophoresis - Thong, Kwai Lin; Puthucheary, S.D.; Pang, T. (1995)
Ribotyping, PCR-ribotyping and pulsed-field gel electrophoresis were used to analyze five serial isolates of Salmonella typhi obtained from a single patient with relapsing typhoid fever over a 7-week period. The 5 isolates were genetically identical by all three methods thus suggesting relapsing infection with the same strain and implying in vivo genomic stability of S. typhi even in the presence of selective pressures of antibiotic treatment and host defenses.